2020
DOI: 10.1111/1467-9817.12326
|View full text |Cite
|
Sign up to set email alerts
|

The effects of glossing on incidental vocabulary learning during second language reading: based on an eye‐tracking study

Abstract: Providing glosses that explain the meanings of unknown words is a common method of promoting learners' learning of new words. Numerous studies have shown that compared with no-gloss condition, glosses benefit the learning of the meaning of new words. This study combines both online (i.e., eye-tracking) and offline (i.e., immediate vocabulary tests) measures to investigate the influences of glosses on incidental vocabulary learning and evaluating the degree to which glossing influences reading behaviour during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In relation to research question 1, the results first showed that all the four groups got higher scores on the posttest than those on pretests on both vocabulary production and recognition tasks, suggesting the effectiveness of multimedia glosses on vocabulary acquisition. In previous research (e.g., Abuseileek, 2011 ; Rouhi and Mohebbi, 2012 ; Ramezanali and Faez, 2019 ; Ouyang et al, 2020 ), the positive effects of multimedia glosses on vocabulary tests have also been found. In addition, students in all four groups achieved better gains on vocabulary recognition tests (overall gains: 14.01, from 14.78 to 28.79) than on vocabulary production tests (overall gains: 6.35, from 3.56 to 9.91), showing that multimedia glosses facilitate learning knowledge of recognition more than learning of recall knowledge.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In relation to research question 1, the results first showed that all the four groups got higher scores on the posttest than those on pretests on both vocabulary production and recognition tasks, suggesting the effectiveness of multimedia glosses on vocabulary acquisition. In previous research (e.g., Abuseileek, 2011 ; Rouhi and Mohebbi, 2012 ; Ramezanali and Faez, 2019 ; Ouyang et al, 2020 ), the positive effects of multimedia glosses on vocabulary tests have also been found. In addition, students in all four groups achieved better gains on vocabulary recognition tests (overall gains: 14.01, from 14.78 to 28.79) than on vocabulary production tests (overall gains: 6.35, from 3.56 to 9.91), showing that multimedia glosses facilitate learning knowledge of recognition more than learning of recall knowledge.…”
Section: Discussionmentioning
confidence: 81%
“…Several studies have confirmed that the adoption of multimedia glosses promote leaners' vocabulary knowledge (e.g., Abuseileek, 2011 ; Rouhi and Mohebbi, 2012 ; Ramezanali and Faez, 2019 ; Ouyang et al, 2020 ). However, the results are inconsistent regarding the effectiveness of different glossing modes on vocabulary learning.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…When some of the participants were asked to infer the meaning of the target words with the text at their disposal, they often failed to do so, which suggests they simply did not recognize the purpose of the appositives. In other studies, where in-text glosses were more clearly signalled as word clarifications, these did yield comparatively good results (Ouyang et al, 2020;Zhang & Webb, 2019, for recent examples). A re-assessment of the effectiveness of in-text glosses may become feasible when more studies comparing in-text and marginal glosses become available.…”
Section: The Location Of Glossesmentioning
confidence: 87%
“…In comparison, eye-tracking (e.g., Ouyang et al, 2020) can provide not only data regarding attention to the glossed items but also regarding additional instances (if any) of the target words in the text. Moreover, it can capture what part of a gloss attracts attention the most (which may be useful, for example, to evaluate the respective contributions of pictorial and textual information in a multimodal gloss) and it can capture how a reader's eyes move back and forth between a gloss and the instance of the word in the text (which may be indicative of the effort the reader puts into establishing a correspondence between the information in the gloss and the contextual use of the word).…”
Section: Establishing Cause-effect Relations: To What Extent Do Learners Engage With Glosses?mentioning
confidence: 99%